Forward Induction in the Battle of Sexes Games - Cooper, Russell; DeJong, Douglas V.; Forsythe, Robert; Ross, Thomas W. (American Economic Review, 1991)
This paper provides experimental evidence on forward induction as a refinement criterion. In the basic extensive form, one of the two players chooses to play a battle-of-the-sexes game or to receive a certain payoff. According to forward induction, choosing to play the game is a signal about intended action. Though the presence of the outside option changes play, the authors find only limited support for the forward-induction hypothesis. The effects of the outside option also reflect the creation of a focal point through the asymmetry created by offering the outside option to one of the two players. Copyright 1993 by American Economic Association.